2020
DOI: 10.1101/2020.08.14.251777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Embodied Cognition and Decision-Making in the Primate Superior Colliculus

Abstract: A popular model of decision-making suggests that in primates, including humans, decisions evolve within forebrain structures responsible for preparing voluntary actions; a concert referred to as embodied cognition. Embodied cognition posits that in decision tasks, neuronal activity generally associated with preparing an action, actually reflects the accumulation of evidence for a particular decision. Testing the embodied cognition model causally is challenging because dissociating the evolution of a decision f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Importantly, in this experiment, monkeys also performed a saccade selection task in which they made saccades to the same two locations as the choice targets, but neither perceptual ambiguity nor orientation discrimination occurred. Here, muscimol did not impair the monkeys' ability to distribute their saccadic choices equally between the two locations, ruling out interpretations based on motor or attentional biases (Jun et al, 2020). An extensive modeling effort revealed that muscimol inactivation produced a decrease in the relative evidence for decisions made to the inactivated field (Jun et al, 2020), consistent with previous modeling efforts in the SC (e.g., Ratcliff et al, 2003Ratcliff et al, , 2007.…”
Section: A B C D Esupporting
confidence: 82%
See 1 more Smart Citation
“…Importantly, in this experiment, monkeys also performed a saccade selection task in which they made saccades to the same two locations as the choice targets, but neither perceptual ambiguity nor orientation discrimination occurred. Here, muscimol did not impair the monkeys' ability to distribute their saccadic choices equally between the two locations, ruling out interpretations based on motor or attentional biases (Jun et al, 2020). An extensive modeling effort revealed that muscimol inactivation produced a decrease in the relative evidence for decisions made to the inactivated field (Jun et al, 2020), consistent with previous modeling efforts in the SC (e.g., Ratcliff et al, 2003Ratcliff et al, , 2007.…”
Section: A B C D Esupporting
confidence: 82%
“…Here, muscimol did not impair the monkeys' ability to distribute their saccadic choices equally between the two locations, ruling out interpretations based on motor or attentional biases (Jun et al, 2020). An extensive modeling effort revealed that muscimol inactivation produced a decrease in the relative evidence for decisions made to the inactivated field (Jun et al, 2020), consistent with previous modeling efforts in the SC (e.g., Ratcliff et al, 2003Ratcliff et al, , 2007. Interestingly, inactivation of cortical area LIP showed impairments only in sensory aspects of decisions and not in decision-making per se (Katz et al, 2016;Zhou and Freedman, 2019).…”
Section: A B C D Ementioning
confidence: 63%